Assessment of the reliability of at-home caregiver-collected anthropometric measurements - Ly, Jenny J.; Sosa, Ana; Heidman, Matthew; Dixon, Matthew F.; Ostolaza, Christian; Dallabrida, Susan M. (Frontiers in Pediatrics, 2024)
Introduction Anthropometric measurements provide valuable information about infant growth patterns and can help identify nutrition, growth, and developmental concerns. With the increasing use of telehealth and decentralized clinical trial approaches, there is potential for caregivers to collect anthropometric measurements at home via teleconference with healthcare providers (HCPs) to monitor infant growth, which indirectly reflects health status. This study aimed to evaluate whether telehealth-guided caregivers can utilize standardized methods and home-use measurement equipment to collect reliable anthropometric measurements compared to HCPs and study nurses. Methods The study compared the weight, length, and head circumference measurements collected by caregivers (n = 8 pairs), pediatric HCPs (n = 7), and study nurses (n = 4), who served as the gold standard comparator group. Four silicone dolls with varied anthropometrics were used as surrogates for human infants. Results Caregiver inter- and intra-observer technical errors of measurement (TEMs) were all equal to or below the maximum allowed error (MAE). For HCPs, only intra-observer TEM for length and inter-observer TEM for HC and length were within the MAE. There was no evidence of bias for either caregiver or HCP measurements compared to the gold standard. Coefficients of reliability (R) were greater than 0.96 for all measurements. Discussion Preliminary results from this study demonstrate that telehealth-guided caregivers can capture accurate and reliable anthropometric measurements compared to HCPs. The results suggest that remote measurement collection allows for more frequent monitoring while reducing the burden on patients and caregivers in primary care and clinical trials such as infant formula growth monitoring studies.